Diabetes as a risk factor of death in hospitalized COVID-19 patients – an analysis of a National Hospitalization Database from Poland, 2020 - Kania, Michal; Koń, Beata; Kamiński, Konrad; Hohendorff, Jerzy; Witek, Przemysław; Klupa, Tomasz; Malecki, Maciej T. (Frontiers in Endocrinology, 2023)
Introduction Diabetes is one of comorbidities in hospitalized COVID-19 patients associated with poor prognosis. In this nationwide retrospective study we evaluated the risk of in-hospital death attributed to diabetes. Methods We analysed data from discharge reports sent to the Polish National Health Fund from 2020 of hospitalized COVID-19 patients. Several multivariate logistic regression models were used. In each model, in-hospital death was estimated with explanatory variables. Models were built either on the whole cohorts or cohorts matched with propensity score matching (PSM). They examined either main effects or included interaction of diabetes with other variables. Results We included 174,621 patients with COVID-19 hospitalized in the year 2020. Among them, there were 40,168 diabetic patients (DPs), and the proportion of DPs in this group was higher than in the general population (23.0% vs. 9.5%, p<0.001). Overall, 17,438 in-hospital deaths were recorded, and the mortality was higher among DPs than non-diabetics (16.3% vs. 8.1%, p<0.001). Multivariate logistic regressions showed that diabetes was a risk factor of death, regardless of sex and age. In the main effect analysis, odds of in-hospital death were higher by 28.3% for DPs than for non-diabetic patients. Similarly, PSM analysis including 101,578 patients, of whom 19,050 had diabetes, showed that the risk of death was higher in DPs regardless of sex with odds higher by 34.9%. The impact of diabetes differed among age groups and was the highest for patients aged 60-69. Conclusions This nationwide study confirmed that diabetes was an independent risk of in-hospital death in the course of COVID-19. However, the relative risk differed across the age groups.